2012
DOI: 10.2319/072711-473.1
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reproducibility of cephalometric measurements performed in full and hemifacial reconstructions derived from cone beam computed tomography

Abstract: Objective: To test the reproducibility and validity of angular measurements from virtual lateral cephalometric radiography (LCR) reconstructions (full and hemifacial on both sides) derived from cone beam computed tomography (CBCT). Materials and Methods: Fifty-eight CBCT and LCR images were selected. CBCT volume data were imported into Nemotec software, and virtual LCR images and tomographic slices from CBCT images were assessed. Three observers digitized landmarks used for 12 angular measurements in CBCT imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
9
0
2
Order By: Relevance
“…With its simplicity of use and high image quality, CBCT has become increasingly popular in orthodontic clinics [8]. Craniofacial measurements derived from CBCT are reproducible and valid [9,10]. CBCT has been used to evaluate maxillary canine impactions and labio-palatal clefts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With its simplicity of use and high image quality, CBCT has become increasingly popular in orthodontic clinics [8]. Craniofacial measurements derived from CBCT are reproducible and valid [9,10]. CBCT has been used to evaluate maxillary canine impactions and labio-palatal clefts.…”
Section: Introductionmentioning
confidence: 99%
“…Grâce à sa facilite d'emploi et à la grande qualite de ses images, le cone beam est de plus en plus utilise par les orthodontistes [8]. Les prises de mesure craniofaciales avec le cone beam sont valides et reproductibles [9,10]. Le cone beam a ete utilise pour evaluer les impactions de canines 3-dimensional analysis of the upper airway while being fast and easy to interpret [11].…”
Section: Introductionunclassified
“…The Op is one of the most reproducible landmarks in a 3DCT analysis. 15 , 16 , 17 When the Op was used for the MRP, as in M2 and M3, the P deviated by up to 3.80 mm. Meanwhile, when the P was used for the MRP, as in M1, the Op deviated by up to 9.33 mm, which results in considerable facial deviation( Table 4 , Fig.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Studies have shown that most measurements are reliable in different situations, such as comparison between CBCT-generated and conventional LC, 10,11 and comparison between CBCT-generated hemifacial and full-face LC to conventional LC. 12 In addition, with CBCT, it is possible to generate a LC of different structures of the head. With the tools that have been made available by computer software, it is possible to eliminate one of the drawbacks of traditional 2D cephalograms (head orientation) and understand how "errors of projection" can influence "errors of identification".…”
Section: Introductionmentioning
confidence: 99%